On Topics Today - Nicholas McKay (Zeitschrift der Gesellschaft für Musiktheorie)
This article surveys the state of so-called topic theory today. It charts its development through two ‘generations’ of ‘topic theorists’. The first is constructed around three influential texts: Leonard Ratner’s seminal book that established the discipline in its own right, Classic music: expression, form and style (1980); Wye Allanbrook’s Rhythmic gesture in Mozart: Le nozze di Figaro and Don Giovanni (1983); and Kofi Agawu’s Playing with signs: a semiotic interpretation of classical music (1991). The second comprises significant advances in topic theory essayed through two further pairs of texts: Robert Hatten’s Musical meaning in Beethoven: markedness, correlation, and interpretation (1994) and Interpreting musical gestures, topics, and tropes: Mozart, Beethoven, Schubert (2004); and Raymond Monelle’s Linguistics and semiotics in music (1992) and The sense of music: semiotic essays (2000).